Estimate a Flexible Link's Shape by the Use of Strain Gauge Sensors. (24th October 2012) - Korayem, M. H.; Shafei, A. M.; Absalan, F.
Abstract : This paper presents a method for estimating the flexible link's shape by finite number of sensors. The position and orientation of flexible link are expressed as a function of curvature of the link. An interpolation technique gives this continuous curvature function from a finite set of the Wheatstone bridge made with strain gauges. For interpolation we can use different functions to find better way for estimation of link's shape. Comparison between different types of function can show us best corresponding with nature of the link. Our case study is a single flexible link robot. A high-precision data logger is used as data acquisition instrument.